Teori Humanisme sebagai Dasar Etika Religius (Perspektif Ibnu Athā’illah Al-Sakandarī) - Chairunnisa Djayadin; Fathurrahman Fathurrahman (Institut Agama Islam Negeri Kendari, 2020)
This study aims to provide a comprehensive and in-depth overview of the results of studying and analyzing the thoughts of Ibn Athā'illah Al-Sakandarī about the theory of humanism as the basis of religious ethics. This research methodology, using the library research method with a philosophical approach, can provide an overview of Ibn Athā'illah Al-Sakandarī's thinking tools about the theory of humanism as a basis for religious ethics as a whole and in-depth. The results of the study showed that humanism, in the view of Islam, means to put forward the humanity that applies fairly and lives peacefully amid differences, this is in line with the thought of Ibn Athā'illah based on the Qur'an and Sunnah. Ibn Athā'illah encourages humans to reach the highest level, namely macrifat, where the values of wisdom are a reflection of the theory of humanism as the construction of religious ethics, then Ibn Athā'illah encourages humans to seek knowledge as well as the development of reason. Ibn Athā'illah encouraged humans to develop according to the conditions of the times by not leaving obedience to God. The thought of Ibn Athā'illah was also acceptable in various circles, scientists, workers and so on, besides that with the value of humanism, harmony in society was formed so that Muslims were not in a debate in carrying out his nature as a human being.